2006
DOI: 10.1093/hmg/ddl001
|View full text |Cite
|
Sign up to set email alerts
|

Imprinted DLK1 is a putative tumor suppressor gene and inactivated by epimutation at the region upstream of GTL2 in human renal cell carcinoma

Abstract: A common deletion at chromosomal arm 14q32 in human renal cell carcinoma (RCC) prompted us to explore a tumor suppressor gene (TSG) in this region. We report that imprinted DLK1 at 14q32, a regulator of adipocyte differentiation, is a candidate TSG in RCCs. DLK1 expression was lost in 39 out of 50 (78%) primary RCC tissues, whereas expression of DLK1 was maintained in every normal kidney tissue examined. DLK1 was expressed in only one of 15 (7%) RCC-derived cell lines. In order to see the biological significan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
74
1

Year Published

2007
2007
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 89 publications
(80 citation statements)
references
References 26 publications
5
74
1
Order By: Relevance
“…Two inhibitors of apoptosis were also up-regulated, baculoviral inhibitor of apoptosis repeat-containing protein 3 (BIRC3) (56) and BCL2-related protein A1 (BCL2A1). These data suggest that dlk1 may modulate the apoptotic responses and corroborate the recent findings that dlk1 may function as a tumor suppressor gene with the ability to suppress tumor growth and increase anchorage-dependent cell death of cancer cells (57). Interestingly, overexpression of Dlk1 in hMSC did not affect their cell growth (15) suggesting that the dlk1 effects on cell growth may be cell type-dependent.…”
Section: Dlk1 Regulates the Cytokines Expression Of Hmscsupporting
confidence: 87%
“…Two inhibitors of apoptosis were also up-regulated, baculoviral inhibitor of apoptosis repeat-containing protein 3 (BIRC3) (56) and BCL2-related protein A1 (BCL2A1). These data suggest that dlk1 may modulate the apoptotic responses and corroborate the recent findings that dlk1 may function as a tumor suppressor gene with the ability to suppress tumor growth and increase anchorage-dependent cell death of cancer cells (57). Interestingly, overexpression of Dlk1 in hMSC did not affect their cell growth (15) suggesting that the dlk1 effects on cell growth may be cell type-dependent.…”
Section: Dlk1 Regulates the Cytokines Expression Of Hmscsupporting
confidence: 87%
“…In contrast, Li et al 49 reported that expression of DLK1 resulted in inhibition of proliferation in hematopoietic cells. Furthermore, Kawakami et al 21 demonstrated that DLK1 expression is lost in human renal cell carcinomas and that its re-expression increases anchorage-independent cell death and suppresses tumor growth in nude mice. The role of DLK1 in human pituitary tumor development requires further investigation.…”
Section: Discussionmentioning
confidence: 99%
“…Loss of imprinting results in a phenotypic spectrum ranging from embryonic lethality to growth retardation and developmental abnormalities. 18,19 In addition, dysregulation of genes at this locus has been found in a subset of human tumors, such as renal cell carcinoma and neuroblastoma, 20,21 suggesting that the DLK1-MEG3 locus plays a role in the development of a number of human neoplasms.…”
Section: Dlk1-meg3mentioning
confidence: 99%
“…Detailed information about one representative sample is given and showed intermediate patterns in three of the eight clones analysed. 27 The possibility exists that the intermediate patterns represent bacterial recombination artefacts. The amplification of bisulphite-treated DNA can generate heteroduplexes, as the parental template strands only differ at specific CpG-sites.…”
Section: Discussionmentioning
confidence: 99%